Les communautés anglophones de la Gaspésie-Îles-de-la-Madeleine : Un profil régional - Committee for Anglophone Social Action (CASA) (2018)

English-speaking Communities of the Gaspésie – Îles-de-la-Madeleine: A Regional Profile - Richardson, Mary; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)

Regional Priorities : QCGN Members 2018 - Quebec Community Groups Network (QCGN) (2018)
This document is a collaborative effort on the part of the regional member organization's of Quebec Community Groups Network to ensure regional priorities are at the fore of the Priority Setting Steering Committee discussions and to establish preferred and inclusive methods of consultation among regional member groups.